Hubungan persepsi dukungan organisasi terhadap kepuasan kerja pada karyawan - Onchi Gemelli Amaradipta; Tulus Winarsunu; Ratih Eka Pertiwi (Fakultas Psikologi, 2022)
Employees contributions are noticed by the company, so efforts made to meet its employees needs are focused on how organizational support is given that employees are satisfied with their jobs. The study used quantitative approach with a correlational design. The sample sampling technique used accidental sampling in which researchers do not use any particular planning in the subject retrieval. Research subjects number 212 with permanent employee criteria for a two-year minimum. The instruments used were surveys of Perceived Organizational Support and Job Satisfaction Survey. The data analysis used is Pearson correlation. The study suggests that there is positive relationship between perceptions of organizational support and job satisfaction with a value of p = .000 (p = < .05). As for the power of the relationship between the two, it is rated strong with value R = .693. This suggests that both variables are unionized in that if perceptions of organizational support are high, the greater the opportunity for job satisfaction arises. Keywords : job Satisfaction, perceived organizational support, supervision, working conditions